Application of an electric field for pretreatment of a feedstock (Laminaria japonica) for dark fermentative hydrogen production. (January 2015) - Jeong, Da-Young; Cho, Si-Kyung; Shin, Hang-Sik; Jung, Kyung-Won
Abstract: When using cellulosic biomass as feedstock for dark fermentative hydrogen production (DFHP), feedstock preparation is essential step for enhancement of biodegradability. In the present work, electric field was newly applied as a novel pretreatment technique to Laminaria japonica, a marine brown algae, as an alternative method for feedstock preparation. A feasibility test was first conducted (20–100 V for 30 min). The highest H2 yield (93.6 mL H2  g −1 dry cell weight (dcw)) was achieved at applied voltage of 60 V, while the performance was decreased from applied voltage of 80–100 V due to increasing formation of hydroxymethylfurfural. Subsequently, electric pretreatment conditions (applied voltage and reaction time) were statistically optimized, and a H2 yield of 102.7 mL g −1  dcw was recorded with applied voltage 58.5 V and reaction time 30 min. This was 96.1% of the predicted value. These findings clearly revealed that the application of electric field as pretreatment method has enormous potential as an alternative method for feedstock preparation in DFHP. Highlights: Electric field was employed as a new pretreatment method for feedstock preparation. Pretreatment conditions (applied voltage and reaction time) were statistically optimized using RSM with CCD. The H2 yield of 102.7 mL g −1  dcw was recorded under optimized conditions; applied voltage of 58.5 V and reaction time of 30 min.